Financing constraints and fixed-term employment contracts: evidence from the 2008-09 financial crisis - Fernandes, Ana P. (2015)
This paper investigates the effects of financing constraints on employment decisions of firms, when it is possible to choose between permanent and fixed-term workers. We use linked employer-employee data for the universe of private sector firms in Portugal, and the 2008-09 financial crisis as a shock for identification. We find that firms in sectors that intrinsically rely more on external finance increased the share of fixed-term employment and hires after the crisis, while the effect for firms with wider access to buyer-supplier credit is relatively lower. At the worker level, workers in sectors that require significant external financing are more likely to be hired with a fixed-term contract after the crisis, while those in sectors that have wider access to supplier credit are less likely. Our results suggest that the crisis induced financially constrained firms to use the more flexible fixed-term contracts more intensively. Credit from suppliers alleviated this effect by potentially providing an alternative source of funds to credit from financial institutions.